Advances in novel biomaterials combined with traditional Chinese medicine rehabilitation technology in treatment of peripheral nerve injury - Liu, Xinhao; Hu, Zekai; Huang, Yixiao; Hu, Lelun; Lu, Jinnuo; Chen, Mengning; Xue, Han; Ma, Shujie; Wan, Jie; Hu, Jun (Frontiers in Neurology, 2024)
Peripheral nerve injuries (PNI) represent one of the primary neuropathies leading to lifelong disability. Nerve regeneration and targeted muscle atrophy stand as the two most crucial factors influencing functional rehabilitation post peripheral nerve injury. Over time, traditional Chinese medicine (TCM) rehabilitation approaches such as acupuncture, Tuina, and microneedles serve as pivot means to activate the regeneration of injured nerve Schwann cells. By promoting axon regeneration, these approaches can accomplish nerve repair, reconstruction, and functional rehabilitation. Although TCM rehabilitation approaches have clinically demonstrated effectiveness in promoting the repair and regeneration of PNI, the related molecular mechanisms remain unclear. This significantly hampers the application and promotion of TCM rehabilitation in PNI recovery. Therefore, deeply delving into the cellular and molecular mechanisms of TCM rehabilitation technologies to foster nerve regeneration stands as the most pressing issue. On the other hand, in recent years, novel biomaterials represented by hydrogels, microfluidic platforms, and new chitosan scaffolds have showed their unique roles in treating various degrees of nerve injury. These methods exhibit immense potential in conducting high-throughput cell and organoid culture in vitro and synthesizing diverse tissue engineering scaffolds and drug carriers. We believe that the combination of TCM rehabilitation technology and novel biomaterials can more effectively address precise treatment issues such as identification of treatment target and dosage control. Therefore, this paper not only summarizes the molecular mechanisms of TCM rehabilitation technology and novel biomaterials in treating peripheral nerve injury individually, but also explores the research direction of precise treatment by integrating the two at both macro and micro levels. Such integration may facilitate the exploration of cellular and molecular mechanisms related to neurodegeneration and regeneration, providing a scientific and theoretical foundation for the precise functional rehabilitation of PNI in the future.